Synergistic effect of VEGF and SDF-1α in endothelial progenitor cells and vascular smooth muscle cells - Yang, Haiyan; He, Cancan; Bi, Yang; Zhu, Xu; Deng, Dan; Ran, Tingting; Ji, Xiaojuan (Frontiers in Pharmacology, 2022)
Vascular endothelial growth factor (VEGF) is a potent agonist of angiogenesis that induces proliferation and differentiation of endothelial progenitor cells (EPCs) after vascular injury. Previous studies have suggested that stromal cell-derived factor 1-alpha (SDF-1α) and VEGF have a synergistic effect on vascular stenosis. The aim of the present study was to investigate whether VEGF and SDF-1α act synergistically in EPCs and vascular smooth muscle cells (VSMCs). In this study, EPCs were isolated from rat bone marrow and their morphology and function were studied. Subsequently, VEGF was delivered into EPCs using an adenoviral vector. Tube formation, migration, proliferation, and apoptosis of VEGF-overexpressing EPCs was analyzed. Then, EPCs were co-cultured with VSMCs in the presence or absence of SDF-1α, the migration, proliferation, apoptosis, and differentiation capacity of EPCs and VSMCs were analyzed respectively. The isolated EPCs showed typical morphological features, phagocytic capacity, and expressed surface proteins. While stable expression of VEGF remarkably enhanced tube formation, migration, and proliferation capacity of EPCs, apoptosis was decreased. Moreover, the proliferation, migration, and differentiation capacity of EPCs in the co-cultured model was enhanced in the presence of SDF-1α, and apoptosis was decreased. However, these effects were reversed in VSMCs. Therefore, our results showed that VEGF and SDF-1α synergistically increased the migration, differentiation, and proliferation capabilities of EPCs, but not VSMCs. This study suggests a promising strategy to prevent vascular stenosis.